Design and operation of the double-cylinder rotary ash cooler for large CFB boilers. (5th May 2020) - Xiao, Huiren; Zhang, Man; Zhang, Yang; Yao, Yuge; Liu, Qing; Yang, Hairui; Lyu, Junfu
Highlights: The difference of heat transfer area is the major influence factor of the output. Contact between the solids and its covered wall dominates the overall heat transfer. Design and operation performance of double-cylinder ash cooler were introduced. Relation between operating performance and rotating speed was provided. Abstract: The bottom ash cooler is an important auxiliary equipment of a circulating fluidized bed (CFB) boiler. As the CFB boiler technology develops, the rotary ash coolers have partially substituted the fluidized bed bottom ash coolers in the industrial practice due to its excellent reliability. To meet the increased output requirement, a double-cylinder rotary ash cooler, rather than the conventional single-cylinder one, was proposed in the present study. This paper provided the design of the double-cylinder rotary ash cooler and presented its application in a 300 MWe CFB boiler. The design parameters, structural features, heat transfer performance, as well as the field trial results were discussed in the present study. In addition, a semi-empirical model was proposed to provide theoretical support for the design principle of the double-cylinder rotary ash cooler. The field trial results showed that the actual output of the installed double-cylinder rotary ash cooler was up to 32 t/h with the ash temperature at the outlet being the designed value, much greater than the value (~23 t/h) of the single-cylinder one at approximately the same size. Particularly, this novel bottom ash cooler had run continuously for more than three years without any maintenances due to its reasonable design.